2018
DOI: 10.3390/insects9040183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Light Spectrum in Helicoverpa armigera Larvae during HearNPV Induced Tree-Top Disease

Abstract: Lepidopteran larvae upon infection by baculovirus show positive photo-tactic movement during tree-top disease. In light of many insects exploiting specific spectral information for the different behavioral decision, each spectral wavelength of light is an individual parsimonious candidate for such behavior stimulation. Here, we investigated the responses of third instar Helicoverpa armigera larvae infected by Helicoverpa armigera nucleopolyhedrovirus (HearNPV) to white (broad-spectrum), blue (450–490 nm), UVA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…For example, many insects depend on visual cues to find and select host plants, to choose mates, and to orient long-distance migrations (Jiggins et al, 2001;Sauman et al, 2005). Light is also an important factor mediating baculovirus-induced climbing behaviour in caterpillars (Bhattarai et al, 2018;Gasque et al, 2019;Han et al, 2018;van Houte et al, 2014). Exposure to light from above, during a specific period post-infection, is required to elicit climbing behaviour in SeMNPV-infected S. exigua larvae (Han et al, 2018).…”
mentioning
confidence: 99%
“…For example, many insects depend on visual cues to find and select host plants, to choose mates, and to orient long-distance migrations (Jiggins et al, 2001;Sauman et al, 2005). Light is also an important factor mediating baculovirus-induced climbing behaviour in caterpillars (Bhattarai et al, 2018;Gasque et al, 2019;Han et al, 2018;van Houte et al, 2014). Exposure to light from above, during a specific period post-infection, is required to elicit climbing behaviour in SeMNPV-infected S. exigua larvae (Han et al, 2018).…”
mentioning
confidence: 99%
“…Third instar larvae of S. exigua infected with SeMNPV, H. armigera infected with HearNPV and L. dispar asiatica infected with LdMNPV displayed positive phototaxis, with infected larvae dying at elevated positions when light was applied from above, while larvae died at low positions in complete dark conditions or when light was provided from below. Uninfected larvae showed no phototactic behaviour as larvae displayed similar movement patterns in light and dark conditions (van Houte et al 2014b;Bhattarai et al 2018a;Bhattarai et al 2018c). Han et al (2018c) further demonstrated that SeMNPV-infected S. exigua larvae needed to be exposed to light provided from above during a defined time period [43 to 50 hours post infection (hpi) for third instars] to exhibit tree-top disease.…”
Section: Baculovirus-induced Tree-top Disease -The Role Of Lightmentioning
confidence: 98%
“…Light was found to play a pivotal role in baculovirus-induced tree-top disease (van Houte et al 2014b;van Houte et al 2015;Bhattarai et al 2018a;Bhattarai et al 2018c). Third instar larvae of S. exigua infected with SeMNPV, H. armigera infected with HearNPV and L. dispar asiatica infected with LdMNPV displayed positive phototaxis, with infected larvae dying at elevated positions when light was applied from above, while larvae died at low positions in complete dark conditions or when light was provided from below.…”
Section: Baculovirus-induced Tree-top Disease -The Role Of Lightmentioning
confidence: 99%
See 1 more Smart Citation